Juridical Review of the Foreigners Traffic Module System (MOLINA) in the Perspective of Law Number 6 of 2011 on Immigration - Jerry Prima; Cokorde Istri Dian Laksmi Dewi; Benyamin Tungga (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Immigration is a vital instrument in safeguarding a nation's sovereignty and security, especially amid increasing global mobility driven by advances in transportation technology and the openness of international relations. As a popular destination for tourism and foreign labor, Indonesia faces significant challenges in monitoring the movement and activities of foreign nationals within its territory. Law Number 6 of 2011 on Immigration regulates various types of residence permits for Foreign Nationals (FNs), including Visit Stay Permits (ITK), Limited Stay Permits (ITAS), Permanent Stay Permits (ITAP), and Special Immigration Stay Permits. To support its supervisory function, the Directorate General of Immigration developed the Foreign Nationals Traffic Module System (MOLINA), a digital information system that records and analyzes real-time data on the movement of FNs. Although MOLINA has proven effective in supporting immigration supervision, administrative services, and enforcement, it lacks explicit legal grounding within the Immigration Law, leading to a legal vacuum and raising concerns regarding administrative legitimacy and personal data protection. Therefore, this research is crucial as a normative legal study of the legality and legal status of MOLINA from the perspective of Indonesia’s positive law. It also responds to the rising number of stay permit violations by foreign nationals in strategic areas such as Bali and aims to encourage regulatory reform in immigration to become more adaptive to technological developments and the demands of fair law enforcement. Keywords: Immigration, Foreign Nationals, Stay Permit.